Mengembangkan modul etnodidaktik berbasis geogebra tentang geometri candi Prambanan untuk menumbuhkan mindset matematika - Valina Ayu Nurhikmah Danti; Abdul Aziz Saefudin; Koryna Aviory; Ch. Eva Nuryani (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2026)
This study aimed to develop a GeoGebra-assisted teaching module based on an ethno-didactical situation using the context of Prambanan Temple to foster students’ mathematical mindset in geometry learning. The study employed a research and development approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The developed module integrated the cultural context of Prambanan Temple, particularly the batur structure, with GeoGebra-based activities to support students’ exploration of the surface area of a rectangular prism. Data were collected through expert validation sheets, student response questionnaires, and mathematical mindset questionnaires. The findings showed that the developed module was valid, practical, and effective for use in learning. The activities in the module helped students face mathematical challenges, try different strategies, revise their constructions, and validate their ideas through GeoGebra. The module also encouraged students to view mistakes as part of the learning process. These findings indicate that culturally grounded digital geometry tasks have the potential to support the development of students’ mathematical mindset